Efficient compression techniques for small devices in rural area networks - Hii, Lu Hui (Universiti Malaysia Sarawak (UNIMAS), 2017)
Rural areas are the geographical areas that are located far away from the cities and there are many small devices being used. Small devices unable to perform complex calculation or intensive operations, causing network congestion often happen in the rural area networks. Compression technique is a workable solution for reducing the congestion in network. Compression technique allows the digital data to be stored as few bit as possible and reduce the transmission time. There are two categories of compression technique, lossy and lossless compression techniques. Both Lightweight DeCompression (LDC) and Lempel-Ziv-Welch (LZW) techniques are from lossless compression. This project investigates the compression ratio and saving percentage of each technique. Besides, the processing time of the technique will be compared. Furthermore, LDC and LZW compression techniques will be implemented into the small devices within rural area networks by using Network Simulator (NS2) simulation tool. The network performance metric like throughput, delay and the packet loss will be determined in the NS2.